Assessing the impact of vertical land motion on twentieth century global mean sea level estimates. Issue 7 (22nd July 2016) - Hamlington, B. D.; Thompson, P.; Hammond, W. C.; Blewitt, G.; Ray, R. D.
Abstract: Near‐global and continuous measurements from satellite altimetry have provided accurate estimates of global mean sea level in the past two decades. Extending these estimates further into the past is a challenge using the historical tide gauge records. Not only is sampling nonuniform in both space and time, but tide gauges are also affected by vertical land motion (VLM) that creates a relative sea level change not representative of ocean variability. To allow for comparisons to the satellite altimetry estimated global mean sea level (GMSL), typically the tide gauges are corrected using glacial isostatic adjustment (GIA) models. This approach, however, does not correct other sources of VLM that remain in the tide gauge record. Here we compare Global Positioning System (GPS) VLM estimates at the tide gauge locations to VLM estimates from GIA models, and assess the influence of non‐GIA‐related VLM on GMSL estimates. We find that the tide gauges, on average, are experiencing positive VLM (i.e., uplift) after removing the known effect of GIA, resulting in an increase of 0.24 ± 0.08 mm yr −1 in GMSL trend estimates from 1900 to present when using GPS‐based corrections. While this result is likely dependent on the subset of tide gauges used and the actual corrections used, it does suggest that non‐GIA VLM plays a significant role in twentieth century estimates of GMSL. Given the relatively short GPS records used to obtain these VLM estimates, we also estimate the uncertainty in the GMSL trend that results from limited knowledge of non‐GIA‐related VLM. Key Points: Tide gauges, on average, are experiencing uplift after removing the impact of GIA Removing non‐GIA VLM from the tide gauges significantly impacts twentieth century GMSL trend estimates GPS VLM errors and the short GPS records do not appear to have a large impact on GMSL estimates